Utilização de modelos moleculares no ensino de estequiometria para alunos do ensino médio - Migliato Filho, José Roberto (2005)
The lack instructional materials for science teaching is a common problem in Brazil, and concerning to chemistry teaching in particular this problem can be observed even in more developed countries. Although molecular models are one of the few materials available for chemistry teaching, they have been hardly used, and this application has been restricted to lessons related to molecular geometry. The lack of materials has specially interfered with stoichiometry teaching, inasmuch as many authors have pointed out that it is one of the most difficult topics for students to understand. This works describes different exercises which were carried out in stoichiometry short courses by using the molecular models as a major teaching resource. These courses were provided for secondary school students in the laboratories of the DQ/UFSCar as well as in two public schools in the city of São Carlos São Paulo, one in a suburb and one in the city center. To collect data, the exercises were performed so that students could use the molecular models. The results showed that such material facilitated the learning process involved in completing exercises related to balancing chemical equations, Lavoisier Law, Proust Law, molar volume, and performance of chemical reactions. It was also verified that the students became independent of simulations with the material during the first exercises at once, and concerning more complex problem, they were almost completely independent. According to the students the use of molecular models made it much easier for them to understand the topics of the short courses. It thus supports researches suggesting that teaching methodologies should prioritize the introduction of new concepts without including mathematical aspects as means of avoiding difficulties in learning chemistry, which are so common in Brazilian Secondary Schools.